The Complexity of Global Capital Flows: Evidence from G20 Countries - Xiaochen Ding; Lu Sui (Discrete Dynamics in Nature and Society)
With the high volatility of capital flow and the imbalance of capital flow between emerging and advanced economies, the complexity of capital flow management is always attractive to researchers and policymakers. This study explores how capital flows in G20 countries are significantly impacted by pull and push factors by using regressions, dynamic system GMM, and Panel-VAR models. The results show that international capital flows are significantly associated with domestic financial development, which is measured by stock-market liquidity and domestic credit. Moreover, international capital flows are affected by push factors, such as the growth of the world economy and fluctuations of the crude oil price. This study controls for real interest rate, foreign currency, and capital restriction because the government and macroprudential policies are critical influences on stabilizing capital flows.